Siamspinops, a new selenopid spider genus from Southeast Asia (Arachnida, Araneae) - Dankittipakul, Pakawin (2009)
Examination of a collection of selenopid spiders from Southeast Asia resulted in recognition of a new genus, Siamspinops gen. nov., which is erected to accommodate four new Southeast Asian species. Siamspinops spinosissimus sp. nov. (the type species; the male and female are described), S. spinosus sp. nov. (female) and S. allospinosus sp. nov. (female) are recorded from Thailand, S. spinescens sp. nov. (female) from the Malay Peninsula.